Produk, Motif Dan Dampak Tenun Tradisional Di Kecamatan Mempura Kabupaten Siak Propinsi Riau - Asmidar; Prihatin, Purwo (Besaung : Jurnal Seni Desain dan Budaya, 2023)
This research relates to traditional weaving produced by a group of craftsmen in Mempura District, Siak Regency. This traditional weaving is a cultural identity that has certain characteristics by displaying traditional values that are in accordance with the philosophy that lives in society. This research problem focuses on the forms of traditional woven products and motifs in Mempura District, Siak Regency which were created by craftsmen in the area. Through an aesthetic, form and motif approach, this type of qualitative research in collecting data through written sources, literature studies, documentation and interviews as well as data analysis concluded that traditional weaving in the area has a variety of product forms, decorative motifs originating from various types of plants. plants, animals and names of natural objects. The presence of traditional weaving in Mempura District, Siak Regency has a cultural, social and economic impact on the community.